EFEKTIFITAS PELAKSANAAN STRATEGI KALAM DALAM PEMBELAJARAN BAHASA ARAB DI MTS AL-JAUHAR DURI - Nova Yanti; Sholehuddin Sholehuddin (Armala, 2020)
Abstact, Research Objectives to determine the process and effectiveness of the Implementation of the Kalam Strategy that has been applied in learning Arabic in Class VII MTs Al-Jauhar Duri. This type of research is qualitative descriptive which is one of the types of research included in the type of qualitative research, with a total population of 151 and a sample of 38 people. The results of this study are that the kalam strategy that has been applied in class VII MTS Al-Jauhar Duri has been effective, the data obtained from questionnaire data that has answered option B as much as 57%, Observation data with an average of 39.2 and Strategy test data kalam with an average grade of 6.8 and Arabic material taught at MTs Al-Jauhar are in accordance with existing guidelines, namely using the book " Modul Alluqhotull Al-Arrabiyyah Al-Awal” Keywords : Effectiveness, Speech Strategy, Learning Arabic